Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am supposed to prove that $x\wedge x = x$ and $x\vee x = x$ follow from the other lattice axioms (associativity, commutativity and absorption).

So far I have $$x = x\vee(x\wedge x) = x\vee(x\wedge(x\wedge(x\vee x))) = x\vee ((x\wedge x)\wedge(x\vee x))$$

My argumentation then was that since $x=x\vee(x\wedge x)$ that either $x\vee x$ or $x\wedge x$ has to be equal to x, after which the other idempotent law would follow. The problem is, that can't be right - $x\vee(y\wedge z)= x$ can be true even though neither y nor z is equal to x (trivial example, $x\neq\emptyset,y=\emptyset,z=\emptyset, x\cup(y\cap z) = x$. I can't really think of anything else either though...

share|improve this question

1 Answer 1

up vote 2 down vote accepted

If $x$ can be written as $x=x\land y$ for any $y$, then we have $$x=x\lor (x\land y) =x\lor x.$$ Now choose $y:=(x\lor x)$.

share|improve this answer
    
You gotta love how these things always seem so stupidly obvious once someone tells you. –  Cubic Nov 29 '12 at 0:06

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.